Solve the exponential equation by the method of relating the bases, first rewriting the equation in the form
![Solve the exponential equation by the method of relating the bases first rewriting the equation in the form class=](https://us-static.z-dn.net/files/d5d/e9d5672bd1efdd50ad1ece9950262b45.png)
Answer:
x = 1/3
Step-by-step explanation:
Both bases can be written as powers of 6.
36^x = (1/6)^(x-1) . . . . . . given
(6^2)^x = (6^-1)^(x -1) . . . . . bases as powers of 6
6^(2x) = 6^(-x+1) . . . . . . . . . simplify exponents
2x = -x +1 . . . . . . . . . . . . . . . .equate exponents of the same base
3x = 1 . . . . . . . add x
x = 1/3 . . . . . divide by 3